Twelve tips for just in time teaching of communication skills for difficult conversations in the clinical setting - Hinkle, Laura Jean; Fettig, Lyle Patrick; Carlos, William Graham; Bosslet, Gabriel (Medical teacher, 2017)
The ability to communicate well with patients and other members of the healthcare team is a vital skill for physicians to have, but one that is often not emphasized in medical education. Learners of all levels can obtain and develop good communication skills regardless of their natural ability in this area, and the clinical setting represents an underutilized resource to accomplish this task. With this in mind, we have reviewed the growing body of literature on the subject and organized our findings into twelve tips to help educators capitalize on these missed opportunities. While our emphasis is helping learners with difficult discussions, these tips can be easily adapted to any other clinical encounter requiring clear communication. Teaching effective communication skills in the clinical setting requires some extra time, but the steps outlined should not take more than a few minutes to complete. Taking the time to develop these skills in our learners will make a significant difference not only their lives but also their patients and their families.